2006
DOI: 10.1677/joe.1.06748
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and neonatal outcomes to recombinant porcine somatotropin administered in the last third of pregnancy to primiparous sows

Abstract: This study aimed to investigate whether the administration of recombinant porcine somatotropin (rpST) late in gestation is associated with increased rates of obstetric and neonatal complications in primiparous sows. From days 80 to 114 of gestational age, 20 primiparous sows were randomly assigned to receive an intramuscular injection of either saline or 6 mg rpST/day. Throughout pregnancy, sows were fed 2·5 to 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Increases in concentrations of glucose and insulin and a decrease in urea nitrogen were also previously reported in growing pigs injected with pST (Wray-Cahen et al, 1991;Dunshea et al, 1992;Caperna et al, 1993). In pregnant gilts, an increase in serum glucose and a decrease in urea nitrogen were observed when pST injections were given from day 108 of gestation onward (Cromwell et al, 1992) and blood glucose was increased with pST injections from days 80 to 114 of gestation (Trujillo-Ortega et al, 2006). Kveragas et al (1986) also reported greater glucose and insulin concentrations in latepregnant sows treated with pST, suggesting a state of insulin resistance.…”
Section: CDsupporting
confidence: 70%
See 1 more Smart Citation
“…Increases in concentrations of glucose and insulin and a decrease in urea nitrogen were also previously reported in growing pigs injected with pST (Wray-Cahen et al, 1991;Dunshea et al, 1992;Caperna et al, 1993). In pregnant gilts, an increase in serum glucose and a decrease in urea nitrogen were observed when pST injections were given from day 108 of gestation onward (Cromwell et al, 1992) and blood glucose was increased with pST injections from days 80 to 114 of gestation (Trujillo-Ortega et al, 2006). Kveragas et al (1986) also reported greater glucose and insulin concentrations in latepregnant sows treated with pST, suggesting a state of insulin resistance.…”
Section: CDsupporting
confidence: 70%
“…Nevertheless, when injections of pST were given in late gestation, effects on piglet birth weight were contradictory. Trujillo-Ortega et al (2006) reported greater piglet birth weight when injecting 6 mg/d of pST from days 80 to 114 of gestation. Yet, when Kveragas et al (1986) injected 10 mg/d of pST during the last 21 d of gestation there was no effect on piglet birth weight.…”
Section: CDmentioning
confidence: 93%
“…At term, placental weights and placental efficiency appear to be similar in sows and gilts, but with a wider range in the sow (van Rens et al, 2005). Some (Sterle et al, 1995;Tmjillo-Ortega et al, 2006), although not all (Gatford et al, 2009), studies have reported increased placental weights after maternal pST treatment in the pig. There is evidence from other species that placental nutrient transport capacity, at least for simple diffusion, is increased by matemal ST treatment in late gestation (Harding et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…19 The use of recombinant somatotropin has also been investigated. One study showed that the daily injection of somatotropin during early gestation (days [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] selectively improved the growth conditions for low-birth weight littermates. 20 Another study demonstrated that the daily treatment of sows in gestation with porcine somatotropin for 75 days increased offspring size at birth.…”
Section: Discussionmentioning
confidence: 99%
“…21 Conversely, the administration of recombinant porcine somatotropin to sows in late pregnancy increased blood glucose levels in sows and offspring as well as the number of neonatal deaths. 22 Gene therapy and EP in the industrial farm setting is relatively novel, yet there are several reports demonstrating the potential of this method. The vaccination of farm animals with plasmid DNA encoding mycobacterial antigens followed by intramuscular (IM) delivery of EP has been shown to improve the primary immune response of goats and cattle.…”
Section: Discussionmentioning
confidence: 99%